OPERATIVE GROUP WITH COMMUNITY HEALTH AGENTS IN PRIMARY CARE: EXPERIENCE REPORT - Pedro Gabriel Silva de Moura; Luiz Rocha Chaves; Ana Karina Leite Costa; Jhéssica Brenda de Sousa da Silva; Thalia dos Santos Moraes; Débora Cardoso Eleres; Elizangela Guedes Gomes; Amanda Ouriques de Gouveia; July Ane Almeida Batalha Rodrigues; Jorge Carlos Menezes Nascimento Junior; Higson Rodrigues Coelho; Mirian Letícia Carmo Bastos (Artefactum - revista de estudos interdisciplinares, 2026)
The present study is an experience report, having as methodological procedure the formation and monitoring of an Operative Group with Community Health Agents on mental health care. This experience was conducted by 6 nursing students of the 9th semester of the Pará State University, Tucuruí-PA, linked to the Ministry of Health through the PET-Health program. The creation of the GO is part of one of the strands of the project formulated by members, entitled: Circles of Culture as an Educational Strategy for Users of the Health System of the Municipality of Tucuruí-PA, seeking the qualification of the integration teaching-service-community. Discussion: In the report of the CHWs, it was clear the concern about the mental health of the community assisted by UBS Matinha, especially after the pandemic of COVID-19. In the use of the group method it was observed advantages in the construction of collective knowledge and approximation among the participants, these characteristics of GO were fundamental to allow that all of the group could feel welcomed, providing the exposure of individual anguishes and needs, which could be discussed and/or reinforced by the other members, with active inclusion of all.